Pertumbuhan Penduduk dan Kualitas Manusia dalam Meningkatkan Ekonomi Syariah di Indonesia (Literatur Review) - Sinambela, Elizar; Harahap, Isnaini; M. Nawawi, Zuhrinal (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
The development of Sharia Economics in Indonesia is currently accelerating. The government is mobilizing all available resources, including human resources. The development of sharia business activities is carried out by strengthening the capacity of sharia business actors. This research aims to determine the impact of population growth and human quality in improving the sharia economy in Indonesia. The research method used is a qualitative method using literature review analysis. The results of this research show that the growth of Indonesia's population, which is predominantly Muslim, has great potential in improving the sharia economy in Indonesia. To improve Sharia Economics, qualified people are needed with qualifications that have soft skills and hard skills. Education and skills are hard skills that must be possessed, while soft skills must be supported by 4 main characteristics, namely having the quality of faith, knowledge, quality of good deeds, and social quality, so that the goals of the sharia economy as a sustainable economy can be realized.